A cross-sectional study to assess menstrual hygiene and school absenteeism related to menstruation among school going adolescent girls of Jalandhar district - Sangha, Navpreet Kaur; Kaur, Prabhjot; Sangha, Faazal Singh; Kaur, Navjot; Singh, Sohrab (International Journal Of Community Medicine And Public Health, 2022)
Background: In India, lack of awareness of safe menstrual hygiene practices is an important issue of adolescent health and is related to various adverse health outcomes. In addition, lack of proper washing facilities is a key factor leading to many adolescent girls missing school due to menstruation. Objectives of current study were to assess the knowledge of menstrual hygiene and its practices among school going adolescent females, associated socio- demographic factors and the prevalence of school absenteeism due to menstruation. Methods: A community based cross sectional study was conducted in the school going adolescent girls of 16 to 19 years age to assess the menstrual hygiene practices and related school absenteeism. A total of 180 participants were evaluated using a self-designed, self-reported and pre-tested questionnaire. Results: Less than half of the participants had prior knowledge of menstruation. Association of education of mother and prior knowledge was statistically significant. Most of the participants missed school due to menstruation. The association between excessive bleeding and absenteeism also showed statistically significant results. Conclusions: The study displayed good results regarding menstrual hygiene practices. Majority of participants had access to sanitary pads and maximum of them followed proper methods of disposal. School absenteeism due to menstruation was seen in more than half of the study population and menstruation had a huge impact on their daily lives.